2014
DOI: 10.5152/jaem.2014.27880
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Base Disorders in the Emergency Department: Incidence, Etiologies and Outcomes

Abstract: Objective: Acid-base disorders (ABDs) are usually correlated with high rates of morbidity and mortality. The objective of this study was to analyze the causes, outcomes, types and incidences of ABDs in patients presenting at the emergency department (ED). Material and Methods:We prospectively analyzed data from patients who presented between January 2011 and May 2011. Data on age, gender, chief complaint, and diagnosis in the ED were collected for ABD cases.Results: Of the 736 cases with an ABD, 173 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…These conditions have been reported to lead to development of acidosis or alkalosis. 18 Normally, the pH of blood plasma is maintained within narrow limits of 7.35–7.45. Most often, acidosis or alkalosis develops when there is a mild disturbance in blood plasma pH outside this range.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions have been reported to lead to development of acidosis or alkalosis. 18 Normally, the pH of blood plasma is maintained within narrow limits of 7.35–7.45. Most often, acidosis or alkalosis develops when there is a mild disturbance in blood plasma pH outside this range.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted in our study that ABD was more common in male than female, which is similar to the findings reported earlier. 4,7 In our study, it was seen that 29% of patients were suffering from simple ABD, whereas 34% of cases were of mixed ABD.…”
Section: Discussionmentioning
confidence: 49%
“…Respiratory alkalosis develops when there is a significant increase in alveolar ventilation relative to carbon dioxide production. If carbon dioxide production remains stable, hyperventilation causes hypocapnia from the excess loss of carbon dioxide resulting in respiratory alkalosis 1. The pH in the blood continues to rise (alkalaemia) due to a shift in the form of bicarbonate to its carbon dioxide form and the reduction of hydrogen ions in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Acid–base disorders (ABDs) are common in hospitalised patients, with a prevalence from 62% to 71% in cross-sectional studies of a pooled population in the intensive care unit (ICU) and emergency department (ED) 1 2. A prospective observational study identified that an elevated serum pH (alkalaemia) was associated with higher levels of morbidity and mortality, with a mortality rate as high as 48.5% in patients with a pH greater than 7.60 3.…”
Section: Introductionmentioning
confidence: 99%